Pharyngeal airway volume and its relationship to the facial morphology in nasal breathing and mouth breathing subjects (A comparative computerized tomography study) - Ahmed M Al-Mayali; Iman I Al-Sheakli (College of Dentistry/ University of Baghdad, 2014)
Background: The value of lateral cephalometric radiographs to evaluate the pharyngeal airway is limited because it provided 2-dimensional (2D) images of complex 3-dimensional (3D) anatomic structures. Three dimensional analyses of the airway volumes are required to understand oral and pharyngeal adaptations in mouth breathing and nasal breathing subjects. The aim of this study was to measure the pharyngeal airway volume and the size of the face, then compare between pharyngeal airway volume in mouth breathing and nasal breathing subjects and find the gender difference in each group, also to study the relation between pharyngeal airway volume and the size of the face. Material and Methods: Fifty patients including 28 males and 22 females with an age ranged between 18-35 years suffered from clinical symptoms of nasal obstruction and mouth breathing was detected by otolaryngologist and sent to be imaged by Brilliance™ 64, Philips multi-detector computed tomography. Twenty normal subjects (10 males and 10 females) were selected as control. Angular and linear variables were measured in addition to the size of the face and the pharyngeal airway volume. Results: A statistically significant relationship between the pharyngeal airway volume and the mode of respiration and between pharyngeal airway volume and genders were detected. The pharyngeal airway volume was larger in nasal breathers than in mouth breathers and it was larger in males than in females. The size of the face was larger in males than females. Conclusion: CT volumetric images provide more reliable and accurate information for measurement of the pharyngeal airway volume, so the changes in the pharyngeal airway volume can be studied before and after surgery and this will aid in selection of the best treatment option in addition to control the relapse after orthodontic treatment with mouth breathing patients.